Fenomena Lesbian, Gay, Biseksual Dan Transgender (Solusi Dan Upaya Pencegahannya) - Yosi Aryanti (HUMANISMA : Journal of Gender Studies, 2019)
The phenomenon of lesbian, gay, bisexual and transgender (LGBT) in millennial times is no longer considered a new thing in society. Previously these behaviors were considered strange for some people, but in an age of increasingly sophisticated technology, this has become commonplace. Today many have openly stated and identified themselves as the identity of LGBT people or as supporters of their development. This large wave of groups striving to be recognized in the eyes of the world has been carried out intensively and continuously. Indonesia as the largest Muslim cannot be separated from the influence and threat of LGBT. This study aims to explore how the phenomenon of LGBT development and illustrate how solutions and efforts to prevent it. This research was compiled using a literature review approach related to LGBT studies. The results of the excavation found that the LGBT movement is no longer just an individual movement but has entered the public sphere. To overcome this condition, in addition to regulations relating to the movement of LGBT people, in the smallest environments in households must prepare methods and ways to prevent the presence of LGBT.